2015
DOI: 10.1002/cncr.29516
|View full text |Cite
|
Sign up to set email alerts
|

Eudaimonic well‐being and tumor norepinephrine in patients with epithelial ovarian cancer

Abstract: Background The impact of psychological well-being on physiologic processes involved in cancer progression remains unclear. Prior research has implicated adrenergic signaling in tumor growth and metastasis. Given that adrenergic signaling is influenced by both positive and negative factors, we examined how two different aspects of well-being (eudaimonic and positive affect) and psychological distress were associated with tumor norepinephrine (NE) in ovarian cancer patients. Methods Women with suspected ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…The previous studies confirmed that emotional intervention was related to prognosis in ovarian cancer . Also, ovarian cancer survivors receiving social support had lower tumor norepinephrine about tumor progression . In addition to ovarian cancer, stress management in breast cancer patients also suppressed the inflammatory reaction induced by anxiety …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The previous studies confirmed that emotional intervention was related to prognosis in ovarian cancer . Also, ovarian cancer survivors receiving social support had lower tumor norepinephrine about tumor progression . In addition to ovarian cancer, stress management in breast cancer patients also suppressed the inflammatory reaction induced by anxiety …”
Section: Discussionmentioning
confidence: 57%
“…20 Also, ovarian cancer survivors receiving social support had lower tumor norepinephrine about tumor progression. 21 In addition to ovarian cancer, stress management in breast cancer patients also suppressed the inflammatory reaction induced by anxiety. 22 In the analysis of the prevalence of mental disorders according to age, each age subgroup showed a tendency to follow the overall result ( Figure 2B).…”
Section: Most Ovarian Cancer Survivors Experienced Psychological Distmentioning
confidence: 99%
“…Previous work has highlighted biological pathways by which social support may mediate survival in ovarian cancer, including angiogenesis, invasion, inflammation, cellular immunity [32, 33] and transcriptional changes in the tumor genome suggestive of less pro-inflammatory and pro-metastatic signaling [34]. Moreover, ovarian cancer survivors with high levels of psychological well-being and/or social support have lower tumor norepinephrine [35, 36], a stress hormone shown to be linked.to tumor progression. These findings suggest the possibility that along with molecular and clinical determinants of long-term survival in ovarian cancer, biobehavioral factors may influence survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol metabolism will produce pregnenolone, progesterone, deoxycorticosterone, corticosterone and aldosterone. Pregnenolone is metabolically converted to 17-OH pregnenolone and dehydroepiandrosterone [125]. Pregnenolone is metabolized further to progesterone, which is converted to 17-OH progesterone followed by formation of either androstenedione or 11-deoxycortisol.…”
mentioning
confidence: 99%
“…We hypothesize that the OH-PCBs and PCB-Sulfates will inhibit SULT1E1 catalysis. The results may influence levels of active hormones estradiol and dehydroepiandrosterone [125] Overall objective of adipogenesis studies in immortalized human adipocytes. Our goal was to observe and measure the toxicity and effects of OH-PCBs before (1), during (2), and after adipocyte differentiation (3).…”
mentioning
confidence: 99%